2013
DOI: 10.1186/2193-1801-2-46
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in migraine-associated gene, atp1a2, and ischemic stroke risk in a biracial population: the genetics of early onset stroke study

Abstract: In a recent meta-analysis migraine was associated with a two-fold increase in stroke risk. While the mechanism driving this association is unknown, one intriguing hypothesis is that migraineurs are genetically predisposed to developing ischemic stroke. Mutations in the ATP1A2 gene are implicated in familial hemiplegic migraine type II and increase the severity of ischemic brain injury in animal models. To further explore these observations, we assessed the association between ATP1A2 polymorphisms, migraine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…These results are compatible to findings in other studies (Reeves et al, 2010) (Harriott et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…These results are compatible to findings in other studies (Reeves et al, 2010) (Harriott et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Only 4 candidate gene studies met our PubMed search criteria examining the genetic associations with IS risk among cases ≤50-year old (Table 3). 5861 The MTHFR C677T variant (rs1801133), a missense variant encoding A222V amino acid change, was reported to be significantly associated with early-onset IS in the meta-analysis of 8 studies with a total of 1093 cases (OR=1.44; P =0.002; Xin et al 58 ). The same study also reported significant associations with APOE (rs7412 and rs429358; OR=2.53; P <0.001) and ITGA2 C807T (rs1126643; OR=1.50; P =0.01), although they also detected evidence for potential publication bias for this latter result, calling the ITGA2 association into question.…”
Section: Methodsmentioning
confidence: 99%
“…59 Consistent with this meta-analysis, the largest single study of unselected early-onset IS cases found no association between FVL and IS (OR=1.0). 60 Harriott et al 61 studied the relationship between 134 polymorphisms of ATP1A2 , a migraine-associated gene, with early-onset IS and only 1 variant reached nominal significance (rs2070704), suggesting no strong association between the ATP1A2 and early-onset IS.…”
Section: Methodsmentioning
confidence: 99%
“…The ATP1A2 gene encodes the α2 subunit of Na+-, K+-ATPase, a plasma membrane enzyme that counter transports Na+ and K+ across cell membranes [21]. ATP1A2 gene mutation result in degeneration of the amygdala and pyriform cortex [22].…”
Section: Resultsmentioning
confidence: 99%